Actor, situation, and context: A framework for delinquency theory integration - Wolfe, Timothy W. (American journal of criminal justice, 1999)
Survey data are presented and discussed as they relate to juvenile involvement in serious and violent delinquency. Juveniles confined in two detention centers were administered self-report questionnaires (n=127). An integrated model that combines social structural variables (i.e., neighborhood disorganization and strain) with social process variables (i.e., parental control, social bond, and delinquent peer associations) was tested by way of path analysis. The data generally support the integrated model, explaining as much as 44% of the variance. Two variables, delinquent peer associations and an overall social bond indicator, directly and significantly predict serious delinquent behavior. Delinquent peer associations are significantly related to neighborhood disorganization, while the social bond is significantly related to parental control and strain. Thus, the data support a systems approach to explaining delinquent behavior, where social structural variables affect social process variables.